Microglial Activation After Systemic Stimulation With Lipopolysaccharide and Escherichia coli - Hoogland, Inge C. M.; Westhoff, Dunja; Engelen-Lee, Joo-Yeon; Melief, Jeroen; Valls Serón, Mercedes; Houben-Weerts, Judith H. M. P.; Huitinga, Inge; van Westerloo, David J.; van der Poll, Tom; van Gool, Willem A.; van de Beek, Diederik (Frontiers in Cellular Neuroscience, 2018)
Background: Microglial activation after systemic infection has been suggested to mediate sepsis-associated delirium. A systematic review of animal studies suggested distinct differences between microglial activation after systemic challenge with live bacteria and lipopolysaccharide (LPS). Here, we describe a mouse model of microglial activation after systemic challenge with live Escherichia coli (E. coli) and compare results with systemic challenge with LPS. Methods: 60 mice were intraperitoneally injected with E. coli (1x104 colony-forming units) and sacrificed at 12, 20, 48 and 72h after inoculation. For 48 and 72h time points, mice were treated with ceftriaxone. 30 mice were intraperitoneally injected with LPS (5 mg/kg) and sacrificed 3 and 48h after inoculation; 48 control mice were intraperitoneally injected with isotonic saline. Microglial response was monitored by immunohistochemical staining with Iba-1 antibody and flow cytometry; and inflammatory response by mRNA expression of pro- and anti-inflammatory mediators. Results: Mice infected with live E. coli showed microglial activation 72h post inoculation, with increased cell number in cortex (p=0.0002), hippocampus (p=0.003), and thalamus (p=0.0001), but not in the caudate nucleus/putamen (p=0.33), as compared to controls. At 72h, flow cytometry of microglia from E. coli infected mice showed increased cell size (p=0.03) and CD45 expression (p=0.03), but no increase in CD11b expression, and no differences in brain mRNA expression of inflammatory mediators as compared to controls. In mice with systemic LPS stimulation, microglial cells were morphologically activated at the 48h time point with increased cell numbers in cortex (p=0.002 ), hippocampus (p=0.0003), thalamus (p=0.007) and caudate nucleus/putamen (p<0.0001), as compared to controls. At 48h, flow cytometry of microglia from LPS stimulated mice showed increased cell size (p=0.03), CD45 (p=0.03) and CD11b (p=0.04) expression. Brain mRNA expression of TNF-α (p=0.02), IL-1β (p=0.02) and MCP-1 (p=0.03) were increased as compared to controls. Interpretation: Systemic challenge with live E. coli causes a neuro-inflammatory response, but this response occurs at a later time point and is less vigorous as compared to LPS stimulation. The E. coli model mimics the clinical situation of infection associated delirium more closely than stimulation with supra-natural LPS.